Estado nutricional e atitudes alimentares de pacientes bariátricos no contexto da pandemia do covid-19 no Brasil - RAMOS, Larissa Oliveira (2023)
Obesity is a chronic disease that affects the population on a global scale, and occurs in a multifactorial way, encompassing both genetic factors and sedentary lifestyle and intake of highcalorie foods. The treatment for obesity comprises cultivating healthy habits, nutritional education, medication assistance, and if these do not obtain positive results, there is surgical treatment through bariatric operations, which over the years has shown good results in the long term, added to the multidisciplinary followup. Thus, the present study aimed to investigate the association between the nutritional status and eating attitudes of bariatric patients in the context of the Covid19 pandemic. This is a crosssectional, descriptive and analytical study, in which a virtual form and the EAT26 test were applied to 412 individuals who underwent bariatric surgery and met the other inclusion criteria expressed in this study. Most participants were female, had completed high school and had a family income of more than seven minimum wages. For statistical analysis, SPSS software, version 21.0, was used. The results of variables were expressed in absolute frequency and for the proportion of continuous variables, mean and standard deviation were used. Pearson's chisquare test was applied to test the association between categorical variables, with analysis of adjusted residuals to identify which categories were associated. For all analyses, the statistical significance level of p<0.05 was considered. The female sex was the predominant group in the research, presenting a higher risk behavior for disturbed eating attitudes, family income of one to two minimum wages proved to be a determining factor for this. The nutritional status of the patients had a mean current BMI of 29.6 kg/m2, representing overweight, although most patients had significant values for disturbed eating attitudes. The prominent technique was gastric bypass and individuals with three and six months of procedure were at risk for TA.